Global research trends on ALK-TKIs in non-small cell lung cancer: a bibliometric analysis - Liu, Yafeng; Han, Zhaojin; Li, Yujia; Zhang, Pengfei; Wang, Qiushi (Frontiers in Pharmacology, 2025)
BackgroundLung cancer remains the leading cause of cancer-related incidence and mortality worldwide. Non-small cell lung cancer (NSCLC) constitutes the most prevalent histological subtype of lung cancer. A notable proportion of NSCLC patients harbor mutations in the anaplastic lymphoma kinase (ALK) gene, and treatment with ALK-TKIs has demonstrated favorable therapeutic efficacy in ALK-positive patients. This study aimed to systematically analyze the body of literature on ALK-TKIs in NSCLC over the past decade from a bibliometric perspective.MethodsRelevant literature on anaplastic ALK-TKIs for the treatment of NSCLC published between 2015 and 2024 was retrieved from the Web of Science Core Collection. Only English-language publications categorized as original researches and reviews were included. Additionally, clinical trial data from the past decade were collected from the ClinicalTrials.gov database. Bibliometric analysis, data processing, and visualization were conducted using CiteSpace, VOSviewer, Excel, and R.ResultsBetween 2015 and 2024, a total of 2,877 publications on ALK-TKIs for NSCLC were identified, with the annual output remaining consistently high, and 198 clinical trials were registered on ClinicalTrials.gov. China contributed the highest number of publications, while Massachusetts General Hospital emerged as the most prolific institution. The most influential journal in this field was Lung Cancer, and Alice T. Shaw was both the most prolific and one of the most influential authors. Keywords such as ‘lorlatinib’, ‘resistance’, ‘circulating tumor DNA’, and ‘immunotherapy’, along with keyword clustering, indicate current research hotspots and future directions in this field.ConclusionThis study provides a comprehensive bibliometric analysis and summary of the developmental trajectory, current research landscape, and future trends in ALK-TKI therapy for NSCLC over the past decade, with individualized and precision medicine remaining the primary direction for the development of ALK-TKI therapy in NSCLC.